Peningkatan Kualitas Pembelajaran Online pada Materi Peredaran Darah Menggunakan Model Problem Based Learning di SMP Muhammadiyah 8 Kota Batu - Eko Susetyarini; Roimil Latifa; Endrik Nurrohman; Abdul Karim Ibrahim; Sri Wahyuni; Husamah Husamah (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2021)
The purpose of this study was to analyze the quality of online learning on blood circulation using a problem based learning model at SMP Muhammadiyah 8 Batu City. The type of research used is a case study (explorative descriptive). The time of the study began in August 2021. The place of research was carried out at SMP Muhammadiyah 8 Batu City. The research procedure includes: preparation and coordination with partner schools as research locations. Coordination with schools and subject teachers involved in research activities to get an agreement, including: 1) the class used for research; 2) model teachers who develop tools and strategies in research activities starting from Plan, Do, and See; 3) the material or topic being taught; and 4) observer who is in charge of observing research activities during open class. The method of collecting research data is by looking at the implementation of the research and discussing the findings in the study. Descriptive data analysis technique. The results showed that, the use of problem based learning models online or online in terms of the implementation of the plan, open class, and see went smoothly, there was an increase in student participation from open class I to open class II. Model teachers use various innovations in learning, including: breakout room google meet, heartbeat media, linoid, quiziz, and problem based learning models.